Socioeconomic effects of COVID-19 in Mexico: A multisectoral approach and policy options - Alan Hernández-Solano; Jhair López-López; Antonio Yúnez-Naude; Yatziry Govea-Vargas (Latin American Economic Review, 2022)
The health crisis caused by the spread of COVID-19 has caused a profound social and economic disruption in Mexico. Our purpose in this paper is to contribute to the knowledge about the economic impact of the pandemic in Mexico and to evaluate social policy options to mitigate its effects. We do so based on a multisectoral-multiplier model and the most recent Social Accounting Matrix for Mexico, with which we estimate the direct and indirect impacts of COVID-19 as well the likely effects of two alternatives for mitigating them: an unconditional cash transfer scheme for households living in poverty, and the establishment of an unemployment insurance program for workers who have lost their jobs during the pandemic. We find that the first alternative alleviates more value added and loss of income, and thus has a greater effect in reducing inequality and the incidence of poverty.
Keywords: 330; Poverty; COVID-19 pandemic; Economywide impacts; Social policies; Income distribution; Poverty